Interactive C# Fundamentals, Core Concepts and Patterns - Sarcar, Vaskaran (Apress, 2018)
Discover object-oriented programming with core concepts of C# in this unique tutorial. The book consists of four major sections which cover 15 core topics - nine of them are dedicated to object-oriented programming, five of them are dedicated to advanced concepts of C#, and one of them is dedicated to design patterns, with coverage of three Gang of Four design patterns with C# implementations. Finally, Interactive C# contains an FAQ section to cover all of these topics. This book uniquely presents a two-way discussion between a teacher and students. So, with this book you will have the feel of learning C# in a classroom environment or with your private tutor. Your teacher will discuss the problems/topics and ask you questions; at the same time, counter questions are provided to clarify points where necessary. You will: Become proficient in object-oriented programming Remake yourself as a great C# programmer Test your skills in C# fundamentals Use Visual Studio to write, compile and execute your code.